DESIGN OF PORTABLE 1KWp SOLAR PV POWER PACK FOR MULTIPLE USES IN RURAL/URBAN AREAS - Kesari, Dr J.P; Goyal, Lavnish (IJRDO - Journal of Electrical And Electronics Engineering, 2015)
The purpose of this work is to develop an energy conversion device which can directly convert the abundant Solar energy available in every part of India into electricity. We would like to serve the people of India who do not have access to electricity (especially in rural areas) by giving them a source of clean energy which is easy to operate and reliable. The Portable Energy Generator will be a boon for rural India as it can easily generate the energy required per day by a rural house hold. It is noise and pollution free. It is portable and can be easily folded, hence no danger of being stolen.